Studi Komparasi Putusan Hakim dalam Isbat Cerai Nikah Siri: Studi Putusan No. 2711/Pdt.G/2023/PA.Kng - Anas Aminudin; Eka (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2026)
Applications for divorce confirmation (isbat divorce) for unregistered (siri) marriages are not an uncommon in religious court. This phenomenon reflects the complex nature of marital practices that are not officially registered in Indonesia, often resulting in legal issues especially when a divorce takes place. One such case is Case Number 2711/Pdt.G/2023/PA.Kng at the Kuningan Religious Court, which serves as the primary focus of this study. The objective of this research is to analyze the legal considerations used by the judge to decide the isbat divorce of a siri marriage and to examine the extent to which the decision aligns with Islamic law and Indonesian positive law, as well as to conduct a comparative study between the two. The research adopts a descriptive-comparative approach, relying entirely on library research, including legal sources, court decision documents, and relevant academic literature. Data analysis was conducted through a process of data reduction, presentation, and conclusion drawing from the collected library materials. The results of the study indicate that: (1) The judge’s consideration in deciding the isbat divorce of the siri marriage was based on administrative and formal legal evidence showing that the marriage was valid under Islamic law, even though it has not been officially registered; (2) From the perspective of Islamic law, the decision is consistent with sharia principles that recognize the validity of a marriage contract based on the religious pillars and conditions of marriage. In terms of positive law, the judge’s consideration refers to the provisions of Law No. 1 of 1974 and the Compilation of Islamic Law as the legal basis for confirming the isbat divorce (3) Comparatively, there is a point of convergence in recognizing the validity of the marriage, but significant differences appear in the administrative aspect as the formal legality recognized by the state.